Childhood Poisoning at a Tertiary Hospital in South West Nigeria - Olatunya, Oladele Simeon; Isinkaye, Ayodeji Olusola; Ogundare, Ezra Olatunde; Oluwayemi, Isaac Oludare; Akinola, Foluso John (Journal of Nepal Paediatric Society, 2016)
Introduction: Poisoning is a preventable cause of childhood morbidity and mortality. Information on childhood poisoning in the developing world is scanty. This study describes the profile of childhood poisoning in a third world hospital. Materials and Methods: Children admitted with poisoning over a 48-months period at the Ekiti State University Teaching Hospital Ado-Ekiti, Southwest Nigeria, were reviewed. Results: It was found that 81 of 5256 admissions representing 1.54% of the total admissions were due to poisoning. Kerosene, Drugs, Alcohol based herbal concoction, pesticides, corrosive agents and carbon monoxide were involved in 37.0%, 22.2%, 19.8%, 8.6%, 6.2% and 6.2% respectively. Accidental and non-accidental intentions were involved in 85.2% and 14.8% cases respectively. Administration of palm oil (oil from Elais guineensis), vomiting induction and herbal concoction were the leading home interventions in 69.1%, 38.3% and 23.5% respectively. One patient required intensive care. There were seven deaths and overall mortality rate was 8.6%. Conclusion: Poisoning remains a cause of childhood morbidity and mortality in Nigeria. Establishment of poisoning information and control centre is recommended among other strategies to combat its scourge. J Nepal Paediatr Soc 2015;35(2):103-110